Le corpus de poésie dite « populaire » comme matériau de recherche pour les sciences humaines et sociales - Youcef Djedi (L’Année du Maghreb)
As a research material, the Maghrebi folk poetry is still little used by human and social sciences, although it is inescapable to figure out what anthropology holds as the « basic cultural personality ». That was this poetry which gave these songs, among which some acquired a liturgical status (or almost). In some qacida-s are kept yet the contents of some important theological and cutural disputes and the marks of big political events.